Reframing Autism in a Mainstream Classroom via the Constructs of Inclusion and Stigma - Xuereb, Kevin; Lawson, Wenn B. (Journal of Intellectual Disability - Diagnosis and Treatment, 2019)
An investigation was undertaken to explore the social environment in a mainstream classroom that housed both non-autistic and autistic students. The research focus was to see if engaging students in a particular programme, successfully reduced stigma. The research is founded upon the concept of autism as part of neurodiversity rather than only disorder. It posits affective and social outcomes of inclusive education can be a reality once stigma is exposed and autism, reframed. The literature reviewed yielded valuable insights into how best to support the rationale of this study to prepare typical classmates for entry of autistic children. Method: Via a single case-study, an engaging and interactive Peer Preparation Programme (PPP) provided opportunities for the pupils and the focus child to interact with each other; enabling them to acquire knowledge about themselves, each other, autism and ways to minimise the negative impact of stigma. Results: Findings indicated a considerable increase in empathetic attitudes, spontaneous interactions, peer awareness, positive peer imitations and peer advocacy. Conclusions: To reframe autism within mainstream classrooms, although conscious this is a single case-study, the program helped pupils comprehend the sensitive issues of social stigma and encourage empathy in practice.